Wherefore art thou, chaperone? - Sumathipala, Sanjeewa (International Journal of Research in Medical Sciences, 2021)
Respect for the dignity of a patient and their privacy are fundamental concerns for all doctors. When an intimate examination is to be undertaken, that respect needs to be especially maintained. The offer of an appropriate chaperone during that examination can help to demonstrate that respect and can safeguard interests of the patient and the doctor.